The Hepatokine FGF21 Increases the Human Spermatozoa Motility - Bourdon, Guillaume; Estienne, Anthony; Chevaleyre, Claire; Ramé, Christelle; Guérif, Fabrice; Brun, Jean-Sébastien; Vasseur, Claudine; Fromont, Gaelle; Plotton, Ingrid; Dufour-Rainfray, Diane; Caldas-Silveira, Erika; Dupont, Joëlle; et al. (Frontiers in Endocrinology, 2022)
Lifestyle, environment and excess body weight are not only associated with an increased risk of metabolic disorders, such as type 2 diabetes, but also to other pathological processes, such as infertility. A hormone produced mainly by the liver called fibroblast growth factor 21 (FGF21) is closely linked to the energy status and is increased in patients suffering from obesity or insulin resistance. Recently, FGF21 has been shown to be associated with female fertility disorders, but no or few data about the role of FGF21 on human male fertility has been described. In the present study, FGF21 was measured in the seminal fluid at a lower level in comparison to the blood level. Thus, in the present in vitro study, we aimed to decipher the FGF21 system in human semen. To evaluate the putative role of FGF21 on spermatozoa function, we incubated human spermatozoa with increasing concentrations of recombinant human FGF21. The FGF21 in seminal fluid is potentially produced by male reproductive tract tissues. In spermatozoa, the FGF21 signal was transduced by the two main receptors FGFR1-c and FGFR3 and the cofactor β-klotho, which are colocalized in the middle piece of spermatozoa and stimulated the PI3K/Akt and MAPK pathways. Finally, in vitro treatment by FGF21 significantly increased sperm motility and ATP levels. Concomitantly, exposure to FGF21 improved the oxidative stress, as a lower ROS level was observed. Overall, these results seem to indicate that the metabolic factor, FGF21, positively modifies the activity and quality of the parameters of human spermatozoa.